Comprehensive evaluation of non-catalytic wet air oxidation as a pretreatment to remove pharmaceuticals from hospital effluents. Issue 7 (1st June 2021) - Boucher, Valérie; Beaudon, Margot; Ramirez, Pedro; Lemoine, Pascal; Volk, Kalyssa; Yargeau, Viviane; Segura, Pedro A.
Abstract : Non-catalytic wet air oxidation removes pharmaceuticals efficiently from hospital wastewater in low chemical oxygen demand conditions. Abstract : Removal of pharmaceuticals from wastewater using chemical processes is a promising solution to mitigate pollution in drinking and surface waters. Non-catalytic wet air oxidation (WAO) is a highly efficient advanced oxidation process that uses air and water at high temperatures and pressures to remove high concentrations of organic compounds from various wastes without use of catalysts. However, the elimination of pharmaceuticals in hospital wastewater with a low organic content by WAO has not yet been sufficiently studied. The objective of the present study was to evaluate both the efficiency and costs of WAO treatment to remove pharmaceuticals present in hospital effluents. First, a laboratory-scale WAO batch unit was used to optimize oxidation temperatures and residence times to achieve high elimination of ten pharmaceuticals of interest in spiked deionized water. Then, optimal conditions were applied to treat hospital wastewater effluents. Results showed that even at low chemical oxygen demand values (<600 mg O2 per L), WAO at 290 °C with 15 min residence time removed between 95.0% and 99.1% of the target compounds spiked at 10 μg L −1 in hospital wastewater. Acute toxicity bioassays using the crustacean Daphnia magna and the bacterium Aliivibrio fischeri showed that the toxicity of hospital wastewater increased after WAO treatment due to the generation of transformation products. However, since the intended use of WAO is as pretreatment for hospital effluents before municipal water treatment, it is not yet clear if WAO treated effluents could affect bacteria in activated sludge. The study included a techno-economic analysis to evaluate capital expenditures (CAPEX) and operational expenditures (OPEX) of an industrial-scale WAO unit to remove pharmaceuticals from the wastewater effluent of a local hospital. This analysis demonstrated that CAPEX for an 86 L min −1 WAO industrial-scale unit was 2.35m (in Canadian dollars), while OPEX was 1.09m, which corresponds to a relative price of 27 per m 3 . Initial investment for the WAO unit might be reduced by up to 44% by employing a preconcentration unit to increase the effluents' chemical oxygen demand in smaller volumes which could also make the process autothermal while reducing WAO's operating expenses by more than 20%.